Efforts to increase consumer interest through price and service quality - Lazuardi, Dedy; Gustina, Ihdina; Rinaldi, Muammar; Amril, Amril (Institute of Computer Science (IOCS), 2024)
This research aims to determine the effect of price on purchase interest at the Sinar Buana Store, to determine the influence of service quality on purchase interest at the Sinar Buana store, to determine the influence of price and service quality on purchase interest at the Sinar Buana store. The research methodology used is a quantitative descriptive method. The type of data used in this research is quantitative data, namely data obtained in the form of numbers or figures. Data sources include primary data and secondary data. Primary data was obtained from the results of distributing questionnaires to respondents, secondary data was obtained from data and literature relating to the problems discussed. The research population that will be used in the research is all consumers who made purchases at the store during the 2020 period, totaling 17,346 consumers. This amount was obtained from transactions during 2020. By using the Slovin formula with an error rate of 10%, a sample size of 100 respondents was obtained. Data were analyzed using multiple linear regression analysis methods. The results showed that price and service quality had a positive and significant effect on purchase interest at the Sinar Buana Store.